PRAKTIK PINJAM MEMINJAM BENIH PADI DALAM TINJAUAN FIQH MUAMALAH (Studi Kasus di Nagari Sungai Jambu) - Ferli Yunanda; Nailur Rahmi (Institut Agama Islam Negeri Batusangkar, 2022)
This study examines the practice of borrowing and borrowing rice seed in Nagari Sungai Jambu, pariangan sub-district. The problem is that in the implementation of lending and borrowing rice seeds at the time of repayment there is a price difference between the returns in the from of rice and paddy. From these problems question arise: 1.) how is the practice of implementing the loan and borrowing agreement for rice seeds in nagari Sungai Jambu, sub-district pariangan. 2.) how does fiqh muamalah review the practice implementing rice seed lending and borrowing contracts in Nagari Sungai Jambu, kec, pariangan. This research is a field research data obtained through interviews and documentation between rice seed owners and rice seed borrowers, after the collected data is processed by means of a research process and systematic compilation of data obtained from interviews, field notes, documentation so that they can be understood by themselves and others another and analysed by 1) collecting data sources related to the problem studied, both rice seed owners and riceseed borrowers. 2) reading, analysing and recording data sources that have been collected from rice seed owner and rice seed borrowers. 3) discussing the problems being reviewed and analising them descriptively, qualitatively, namely by looking directly at the study found that the practice of implementing rice seed lending and borrowing contracts in Nagari Sungai Jambu district, pariangan is a loan agreement between the seed owner and the seed borrower with different forms of return, both in terms of price and object, namely rice and rice. The price difference does not include usury because the price in the market is not required by the owner of the seed pack, because there are benefits in the form of helping and avoiding waste.